Genome Analysis of a Verrucomicrobial Endosymbiont With a Tiny Genome Discovered in an Antarctic Lake - Williams, Timothy J.; Allen, Michelle A.; Ivanova, Natalia; Huntemann, Marcel; Haque, Sabrina; Hancock, Alyce M.; Brazendale, Sarah; Cavicchioli, Ricardo (Frontiers in Microbiology, 2021)
Organic Lake in Antarctica is a marine-derived, cold (-13ºC), stratified (oxic-anoxic), hypersaline (>200 gL-1) system with unusual chemistry (very high levels of dimethylsulfide) that supports the growth of phylogenetically and metabolically diverse microorganisms. Symbionts are not well characterized in Antarctica. However, unicellular eukaryotes are often present in Antarctic lakes and theoretically could harbor endosymbionts. Here we describe Candidatus Organicella extenuata, a member of the Verrucomicrobia with a highly reduced genome, recovered as a metagenome-assembled genome (MAG) with genetic code 4 (UGA-to-Trp recoding) from Organic Lake. It is closely related to Candidatus Pinguicocccus supinus (163,218 bp, 205 genes), a newly described cytoplasmic endosymbiont of the freshwater ciliate Euplotes vanleeuwenhoeki (Serra et al., 2020). At 158,228 bp (encoding 194 genes), the genome of Ca. Organicella extenuata is among the smallest known bacterial genomes, and similar to the genome of Candidatus Pinguicocccus supinus (163,218 bp, 205 genes). Ca. Organicella extenuata retains a capacity for replication, transcription, translation, and protein-folding, while lacking any capacity for the biosynthesis of amino acids or vitamins. Notably, the endosymbiont retains a capacity for fatty acid synthesis (type II) and iron-sulfur (Fe-S) cluster assembly. Metagenomic analysis of 150 new metagenomes from Organic Lake and more than 70 other Antarctic aquatic locations revealed a strong correlation in abundance between Ca. Organicella extenuata and a novel ciliate of the genus Euplotes. Like Ca. Pinguicocccus supinus, we infer that Ca. Organicella extenuata is an endosymbiont of Euplotes, and hypothesize that both Ca. Organicella extenuata and Ca. Pinguicocccus supinus provide fatty acids and Fe-S clusters to their Euplotes host as the foundation of a mutualistic symbiosis. The discovery of Ca. Organicella extenuata as possessing genetic code 4 illustrates that in addition to identifying endosymbionts by sequencing known symbiotic communities and searching metagenome data using reference endosymbiont genomes, potential exists to identify novel endosymbionts by searching for unusual coding parameters.